Newly discovered diversity in the tropical fern genus Metaxya based on morphology and molecular phylogenetic analyses - Cárdenas GG; Tuomisto H; Lehtonen S (SPRINGER LONDON LTD, 2022)
For a long time, the genus Metaxya was treated as monotypic with a single species, M. rostrata. A second species, M. lanosa, was described in 2001 on the basis of morphological features and rbcL gene sequences with a suggestion that the genus may contain even more species. We have now systematically compared morphological traits in a large number of Metaxya specimens collected in tropical America. We have also carried out phylogenetic analyses of 32 Metaxya and 5 outgroup specimens based on four markers of the plastid genome (rbcL, matK, and rps4 genes, and trnG-trnR intergenic spacer). Based on the morphological variation among the Metaxya specimens, we accept six distinct species, three of which we describe as new in this paper. Molecular phylogenetic analyses resolved five distinct clades. Four of these corresponded with the morphologically delineated species (M. contamanensis sp. nov., M. elongata sp. nov., M. lanosa, and M. parkeri). The fifth clade contained all the individuals of the remaining two species, of which M. rostrata was rendered paraphyletic by M. scalaris sp. nov. being nested within it. Since M. scalaris was resolved as monophyletic, and the two are clearly distinguishable morphologically, we consider them true species despite the incomplete genetic differentiation.